2008
DOI: 10.1128/jvi.01650-07
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Regulation of RIG-I-Mediated Antiviral Signaling by Interferon-Induced ISG15 Conjugation

Abstract: RIG-I senses intracellular virus-specific nucleic acid structures and initiates an antiviral response that induces interferon (IFN) production, which, in turn, activates the transcription of RIG-I to increase RIG-I protein levels. Upon intracellular poly(I:C) stimulation, however, the levels of RIG-I protein did not correlate with the expression patterns of RIG-I transcripts. When the ISG15 conjugation system was overexpressed, ISG15 was conjugated to RIG-I and cellular levels of the unconjugated form of RIG-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
185
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(194 citation statements)
references
References 43 publications
8
185
1
Order By: Relevance
“…Many proteins are known to modify the RIG-I pathway and the subsequent cytokine signal transduction (34,51,57,58), but the role of miRNA-mediated regulation is only beginning to emerge. Thus, the level of receptor expression is the first and likely effective point at which miRNAs exert their functions, but few studies have focused on the regulation of RIG-I expression by miRNAs (18).…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins are known to modify the RIG-I pathway and the subsequent cytokine signal transduction (34,51,57,58), but the role of miRNA-mediated regulation is only beginning to emerge. Thus, the level of receptor expression is the first and likely effective point at which miRNAs exert their functions, but few studies have focused on the regulation of RIG-I expression by miRNAs (18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ISG15 can have an antiviral effect on Sindbis virus, influenza virus, HSV, human immunodeficiency virus (HIV) and Ebola virus (Lenschow et al, 2005(Lenschow et al, , 2007Okumura et al, 2006;Zhang et al, 2007), but ISGylation does not contribute to murine susceptibility to lymphocytic choriomeningitis virus and vesicular stomatitis virus , nor to hepatitis B virus replication in ISGylation-deficient mice (Ube1L 2/2 ) (Kim et al, 2008a). Although ISG15 may also promote viral production by acting as a negative regulator of the innate immune response through its conjugation to RIG-I (Kim et al, 2008b), this mechanism is unlikely to contribute to our observed effects, as Huh7.5 cells are deficient in RIG-I (Sumpter et al, 2005). Our data suggest that HCV exploits the ISG15/ISGylation pathway to increase HCV production: overexpression of ISG15, which increases ISGylation in Huh7.5 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst these studies suggest a general role for ISG15 as an antiviral agent, a recent report found that ISG15 can inhibit IFN responses after infection by Newcastle disease virus (Kim et al, 2008a). ISGylation of the antiviral RIG-I enzyme inhibited IFN signalling in MEF cells (Kim et al, 2008b). Thus, ISG15 inhibits virus production for many viruses, but may promote production of some.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), endosome/lysosome-localized molecules (Rab7b, 22,23 CLM-3 24 ), gene transcription coactivators (beta-catenin 25 ), antigen-presenting molecules (MHC I and MHC II 26,27 ), and even HSP70, 28 HSP70L1 29 and NGF. 30 Recently, RIG-I signal pathway regulation was extensively investigated; [31][32][33][34] however, the full anti-inflammatory response mechanisms and the precise finetuning of this process still remain incompletely elucidated.…”
Section: Introductionmentioning
confidence: 99%